INTERNATIONAL LAW STANDARDS REGARDING SUBSTANTIVE PETTY OFFENCES LAW - Maciej Iwański (Revija za kriminologiju i krivično pravo)
This article attempts to identify and analyse, in the light of the provisions of the acts of international law, the following issues belonging to the substantive part of the law on petty offences: the general problem of criminalization in petty offenses law and; the question of the criminal nature of the law of petty offenses, and thus the application of individual provisions to it and the resulting guarantees appropriate to that law; the application of the principle of guilt on the basis of the analysed regulations as a premise for assigning liability; the principle of ne bis in idem; the principle of nullum crimen nulla poena sine lege, especially in so far as it derives from the principle of lex mitior retro agit.